2008
DOI: 10.1126/science.1155244
|View full text |Cite
|
Sign up to set email alerts
|

Early Forebrain Wiring: Genetic Dissection Using Conditional Celsr3 Mutant Mice

Abstract: Development of axonal tracts requires interactions between growth cones and the environment. Tracts such as the anterior commissure and internal capsule are defective in mice with null mutation of Celsr3. We generated a conditional Celsr3 allele, allowing regional inactivation. Inactivation in telencephalon, ventral forebrain, or cortex demonstrated essential roles for Celsr3 in neurons that project axons to the anterior commissure and subcerebral targets, as well as in cells that guide axons through the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
192
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(202 citation statements)
references
References 25 publications
10
192
0
Order By: Relevance
“…Ceslr3 conditional knockout mice, we found that Ceslr3 is required in both projecting axons and guidepost cells for axonal pathfinding [44][45][46] . When Celsr3 is removed from the guidepost cells of the basal forebrain using Dlx5/6-Cre, This mimics the flamingo function in regulating tissue polarity as suggested.…”
Section: Two Mouse Mutants Of Celsr1 Have Been Identified Inmentioning
confidence: 81%
“…Ceslr3 conditional knockout mice, we found that Ceslr3 is required in both projecting axons and guidepost cells for axonal pathfinding [44][45][46] . When Celsr3 is removed from the guidepost cells of the basal forebrain using Dlx5/6-Cre, This mimics the flamingo function in regulating tissue polarity as suggested.…”
Section: Two Mouse Mutants Of Celsr1 Have Been Identified Inmentioning
confidence: 81%
“…We described previously conditional and constitutive Celsr3 mutant mice 23 . The mutant Celsr2 allele was generated by insertion of a targeting vector containing an internal ribosomal entry site (IRES) and the LacZ gene, into exon 23 of the Celsr2 gene, preserving the endogenous splice acceptor ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive Celsr3 mutant mice die at P0 19 . Therefore, we produced Celsr3|Emx1 mice, in which Celsr3 is inactivated in dorsal telencephalon, including the ependymal layer in the roof of lateral ventricles 23 . In these mice, referred to as "Celsr3", cilia were indistinguishable from that in WT cells (Compare Fig.…”
Section: Celsr2 and 3 Have Redundant Functions In Ciliogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of DN-Cadherin in fly embryos induces defasciculation and misorientation of axons (Iwai et al 1997). In null mouse mutants of Celsr3, an atypical cadherin/Drosophila flamingo homologue, the extension of subcortical projections to and within the cortex are impaired and cortex-specific inactivation impairs projections to the cortex (Zhou et al 2008). In the L1 null mouse thalamocortical axons are hyper-fasciculated and make guidance errors (Wiencken-Barger et al 2004).…”
Section: Adhesive Cuesmentioning
confidence: 99%